Imaging the dynamics and microstructure of fibrin clot polymerization in cardiac surgical patients using spectrally encoded confocal microscopy. Issue 8 (21st May 2021) - Tshikudi, Diane M.; Simandoux, Olivier; Kang, Dongkyun; Van Cott, Elizabeth M.; Andrawes, Michael N.; Yelin, Dvir; Nadkarni, Seemantini K.
Abstract: During cardiac surgery with cardiopulmonary bypass (CPB), altered hemostatic balance may disrupt fibrin assembly, predisposing patients to perioperative hemorrhage. We investigated the utility of a novel device termed spectrally‐encoded confocal microscopy (SECM) for assessing fibrin clot polymerization following heparin and protamine administration in CPB patients. SECM is a novel, high‐speed optical approach to visualize and quantify fibrin clot formation in three dimensions with high spatial resolution (1.0 μm) over a volumetric field‐of‐view (165 × 4000 × 36 μm). The measurement sensitivity of SECM was first determined using plasma samples from normal subjects spiked with heparin and protamine. Next, SECM was performed in plasma samples from patients on CPB to quantify the extent to which fibrin clot dynamics and microstructure were altered by CPB exposure. In spiked samples, prolonged fibrin time (4.4 ± 1.8 to 49.3 ± 16.8 min, p  < 0.001) and diminished fibrin network density (0.079 ± 0.010 to 0.001 ± 0.002 A.U, p  < 0.001) with increasing heparin concentration were reported by SECM. Furthermore, fibrin network density was not restored to baseline levels in protamine‐treated samples. In CPB patients, SECM reported lower fibrin network density in protaminized samples (0.055 ± 0.01 A.U. [Arbitrary units]) vs baseline values (0.066 ± 0.009 A.U.) ( p  = 0.03) despite comparable fibrin time (baseline = 6.0 ± 1.3, protamine = 6.4 ± 1.6 min, p  = 0.5). In these patients, additional metrics including fibrin heterogeneity, length and straightness were quantified. Note, SECM revealed that following protamine administration with CPB exposure, fibrin clots were more heterogeneous (baseline = 0.11 ± 0.02 A.U, protamine = 0.08 ± 0.01 A.U, p  = 0.008) with straighter fibers (baseline = 0.918 ± 0.003A.U, protamine = 0.928 ± 0.0006A.U. p  < 0.001). By providing the capability to rapidly visualize and quantify fibrin clot microstructure, SECM could furnish a new approach for assessing clot stability and hemostasis in cardiac surgical patients.